A Multifunctional Pincer Ligand Supports Unsaturated Cobalt: Five Functionalities in One Pincer. Issue 33 (15th May 2017) - Polezhaev, Alexander V.; Chen, Chun‐Hsing; Losovyj, Yaroslav; Caulton, Kenneth G.
Abstract: A pyridyl pincer ligand was developed to incorporate steric bulk, through a P t Bu2 arm, and proton responsivity, through a pyrazole pincer ligand arm, together with reactivity at benzylic hydrogen and redox activity within a 1, 4 diazabutadiene moiety. Binding it to CoCl2 yielded square‐pyramidal [(PNNH)CoCl2 ], which was deprotonated by Li[N(SiMe3 )2 ] to form [Li(THF)2 PNNCoCl2 ]. Reduction of this LiCl adduct with KC8 under CO atmosphere led to formation of Co I mono‐ and dicarbonyl complexes, which can be protonated but also further deprotonated at the benzylic CH group to give a dearomatized pyridyl group. The ligand was characterized in its neutral, monoanionic, and dianionic forms, and the anions were shown to exist as intimate ion pairs with Li + bound to pyrazolate N and chloride bound to Lewis acidic cobalt. X‐ray photoelectron spectroscopy was used to assay both Li content and cobalt oxidation states. The general character of binding of LiCl to a metal complex acidic at metal and nucleophilic at ligand (pyrazolate Nβ) is discussed, as are potential catalytic applications of the concept. Abstract : Five in one : A pyridyl pincer ligand was designed to incorporate five different functionalities through P t Bu2 and pyrazole pincer ligand arms (see figure). Ligand properties in neutral, monoanionic, and dianionic form were investigated in Co I and Co II complexes. The concept of a single‐molecule frustrated Lewis pair (FLP) is discussed, and an alkali metal chloride was used as a model substrate to show FLP behavior.